International secondary science grade 6 - Fullick, Ann (Karachi Oxford university press, 2023)
The Oxford International Secondary Science book for Grade 6offers a comprehensive range of activities designed to reinforce key scientific concepts and skills. It provides practice exercises aligned with the curriculum, including questions that cover topics in biology, chemistry, and physics. The workbook aims to help students consolidate their learning, develop critical thinking, and prepare for assessments with engaging and varied tasks.